Delayed feedback between adaptive reservoir operation and environmental awareness within water supply-hydropower generation-environment nexus. (15th April 2022) - Wu, Zhenhui; Liu, Dedi; Mei, Yadong; Guo, Shenglian; Xiong, Lihua; Liu, Pan; Yin, Jiabo; Zeng, Yujie
Abstract: In order to ensure sustainable coevolution of water supply, hydropower generation and environment (WHE), the impact of the delayed feedback between adaptive reservoir operation and environmental awareness on WHE nexus is explored in this paper through comprehensive analysis incorporating the policy, social, economic, and environmental factors. The WHE nexus states referring to water storage in reservoir, population, water use, hydropower generation, environmental awareness, and behavior response of community, have been mimicked using the WHE model. The delaying time caused by the delayed feedback can be estimated from the state processes through two indexes (i.e., response delay and recovery delay). Progressive Optimality Algorithm-Particle Swarm Optimization (POA-PSO) hybrid algorithm is adopted to search for an optimal water level process and water transfer. Moreover, the model parameter sensitivity analysis is conducted to determine the dominant model parameters affecting the time delays. Taking Jiayan reservoir as a case study, the Nash-Sutcliffe Efficiency coefficients of the WHE nexus model are above 0.5 in both calibration and validation period. The delay time between environmental awareness and decision preferences ranges from 0 to 8 years under parameter variations. The decision preference has a quicker response to the rise of the water shortage awareness (0.4 years) than the ecological awareness (5.3 years). The most sensitive parameters affecting the delay times are the response rate, decay rate, and threshold of environmental awareness. The proposed model helps us to understand the feedback among adaptive reservoir operation, environmental awareness and decision preferences, and further gives a new access to make effective and scientific long-term adaptive reservoir operation for the human society-environment coupled system. Highlights: Quantifying delay effects by Water Supply-Hydropower Generation-Environment nexus. Environment system has higher delay when it gets worse compared to other systems. Environmental awareness dominates the feedback among the state variables in nexus. The most sensitive model parameters affecting time delays of WHE nexus are found.